1989
DOI: 10.1111/j.1745-4514.1989.tb00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Low-Molecular Weight Basic Albumin Fraction From Rapeseed (Brassica Napus L.) by Acetylation Part 1. Chemical and Physicochemical Aspects

Abstract: The chemical and physicochemical changes of the low‐molecular weight basic albumin fraction from rapeseed, as a function of degree of acetylation, were studied using amino and ester groups analyses, PAGE electrophoresis, isoelectric focusing, viscometry, circular dichroism and fluorescence spectroscopy. The surface hydrophobicity was evaluated by means of the ANS fluorescence probe technique. The protein was readily acetylated at the amino groups by addition of acetic anhydride. Acetylation of amino acid hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These data point to considerable changes in the globulin spatial structure, whereas that of napin changed only slightly owing to stabilization by disulfide bridges. A marked increase of the surface hydrophobicity at high degrees of acetylation, which has been observed for napin (23) and faba bean 11S globulin (24), can also be assumed for the rapeseed globulin component. In the latter, the hydrophobicity increase should be due both to the attachment of hydrophobic acetyl residues and to intrinsic factors that became evident by exposing buried hydrophobic residues after unfolding of the protein.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These data point to considerable changes in the globulin spatial structure, whereas that of napin changed only slightly owing to stabilization by disulfide bridges. A marked increase of the surface hydrophobicity at high degrees of acetylation, which has been observed for napin (23) and faba bean 11S globulin (24), can also be assumed for the rapeseed globulin component. In the latter, the hydrophobicity increase should be due both to the attachment of hydrophobic acetyl residues and to intrinsic factors that became evident by exposing buried hydrophobic residues after unfolding of the protein.…”
Section: Resultsmentioning
confidence: 87%
“…Although there is a lack of detailed information on conformational changes of the rapeseed globulin cruciferin after acetylation, the existing knowledge on structural changes in succinylated cruciferin (22) and acetylated napin (23), as well as those in acetylated plant globulin homologous to cruciferin (24), may be used to interpret the functionality of acetylated rapeseed protein isolates. These data point to considerable changes in the globulin spatial structure, whereas that of napin changed only slightly owing to stabilization by disulfide bridges.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the influence of the blocking degrees have shown a direct dependence of the ratio of the amount of reagents to reactive groups. By modification of rapeseed albumin, an N-blocking degree of 98 % could be obtained with a molar ratio of acetic anhydride to all reactive groups of 1.1 [9]. On the other hand, acetylation of rapeseed globulin and rapeseed protein isolates lead to N-blocking of 62 % and > 80 %, respectively, with a mass ratio of 0.20 g acetic anhydride per g protein [26,27].…”
Section: Chemical Composition Of Rapeseed Protein Samplesmentioning
confidence: 99%
“…The vicilin content amounted to e4% as determined with SDS-polyacrylamide gel electrophoresis by Schwenke et al (1994). Legumin acetylation was performed according to the procedure of Schwenke et al (1989). The legumin samples were dialyzed against distilled water and freeze-dried just after preparation.…”
Section: Protein Studies Legumin Preparation and Acetylationmentioning
confidence: 99%